The effect of liraglutide on metabolic and reproductive outcomes in infertile women with PCOS: A prospective cohort study - Rossella Cannarella; Aldo E. Calogero; Federica Barbagallo; Cristina Petralia; Antonio Aversa; Rosita A. Condorelli; Sandro La Vignera (Human Nutrition & Metabolism)
Objective: To prospectively evaluate the effects of the administration of liraglutide plus calorie deprivation, metformin plus calorie deprivation, or calorie deprivation alone on hirsutism, metabolic profile, and ovarian reserve in infertile patients with polycystic ovary syndrome (PCOS). Patients and methods: This is a prospective observational study conducted on 80 insulin-resistant and infertile PCOS women. Enrolled patients received liraglutide (Saxenda®) + calorie deprivation (Group 1, n = 50), metformin + calorie deprivation (Group 2, n = 15), or calorie deprivation only (Group 3, n = 15). Endpoints were assessed in all patients before and after 120 days. Results: At the end of treatment, BMI was significantly reduced in all groups, while the HOMA index decreased statistically significantly only in groups 1 and 2. Hormonal evaluation showed that serum SHBG and progesterone levels increased significantly in all three groups, while AMH levels significantly decreased in groups 1 and 3. Finally, the Ferriman-Gallwey score improved significantly in all groups. Percentage of decrease vs. baseline in BMI, HOMA index, AMH, Ferriman-Gallway score, and of increase in SHBG were higher in Group 1 than in Group 2 and Group 3. The percentage of increase in progesterone in Group 1 and Group 2 was higher than in Group 3. Conclusion: The results support the use of liraglutide in insulin-resistant and infertile women with PCOS. The improvement in AMH and progesterone following liraglutide administration could be clinically useful in preparation for controlled ovarian hyperstimulation if patients with PCOS need to resort to an assisted reproductive technique.